System Evaluation and Accounting Procedures for Disbursing Cash Using Supply Money (Up) At The South Halmahera Regency Social Service - RUNTUKAHU, Betania; WALANDOUW, Stanley Kho; KINDANGEN, Wulan D. (Journal of Governance, Taxation and Auditing, 2024)
SKPD accounting systems and procedures include processes that start with recording, summarizing, and reporting finances in APBD accountability. Cash disbursement is a resource component that is very important in implementing programs for development planned by a local government. Supply Money is a work advance in a certain amount given to the Expenditure Treasurer (BP) to finance the daily operational activities of the Work Unit or to finance expenses which, according to their nature and purpose, are not possible to do through a direct payment mechanism. The goal to be achieved by researchers is to evaluate the application of systems and accounting procedures for cash disbursements using supply money (UP) at the South Halmahera Regency Social Service by Minister of Home Affairs Regulation (Permendagri) No. 77 of 2020. The method of analysis in this study is descriptive qualitative analysis. The results of the study show that the System and Procedures for Supply Money (UP) at the South Halmahera Regency Social Service Service are not by Minister Of Home Affairs Regulations Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management, because there are several procedures, namely procedures for Warrants for Paying Supply Money (SPM-UP) and procedures Inappropriate Warrant for Disbursement of Supply Funds (SP2D-UP) and no Verification Letter from the Financial Administration Officer (PPK-SKPD) attached.